Stefan George: Von einer Begegnung (1890) - Klaus Wieland (Recherches Germaniques)
First, the article discusses the systematic theories of the lyric by Dieter Lamping, Rüdiger Zymner and Klaus W. Hempfer, examines their transhistorical and transcultural claim to universal validity and raises the question of how far these classificatory theories can also be used for the interpretation of poems. Subsequently, it analyzes Stefan George’s famous poem Von einer Begegnung as an example of German turn-of-the-century poetry, taking into consideration the pre-texts of Dante, Petrarch and Baudelaire to which George´s poem refers intertextually. Its topic is a unique, fleeting encounter of the lyrical subject with an unknown woman that is hymned and at the same time elegized because it cannot be repeated. Finally, George’s Von einer Begegnung is situated in its social and literary context, whereby its attitude towards the technological and social modernism will be more narrowly defined.